A Desulfurative Strategy for the Generation of Alkyl Radicals Enabled by Visible‐Light Photoredox Catalysis. (3rd May 2018) - Xue, Fei; Wang, Falu; Liu, Jiazhen; Di, Jiamei; Liao, Qi; Lu, Huifang; Zhu, Min; He, Liping; He, Huan; Zhang, Dan; Song, Hao; Liu, Xiao‐Yu; et al.
Abstract: Herein, we present a new desulfurative method for generating primary, secondary, and tertiary alkyl radicals through visible‐light photoredox catalysis. A process that involves the generation of N‐centered radicals from sulfinamide intermediates, followed by subsequent fragmentation, is critical to forming the corresponding alkyl radical species. This strategy has been successfully applied to conjugate addition reactions that features mild reaction conditions, broad substrate scope (>60 examples), and good functional‐group tolerance. Abstract : 1°2°3° – leicht gemacht : Eine neue Desulfurierungsmethode zur Herstellung von primären, sekundären und tertiären Alkylradikalen durch Photoredoxkatalyse mit sichtbarem Licht wird vorgestellt. Der Schlüsselprozess zur Bildung der Alkylradikalspezies ist die Bildung von N‐zentrierten Radikalen aus Sulfinamid‐Zwischenstufen mit anschließender Fragmentierung.